When law is insufficient: Law & Economics in the Aspec vs. Cineplex and Cinemark case - Segovia Trocones, Enzo (2020)
The present paper is based on the importance of use law and economics, in the first place, explaining how it is possible the combined use of it in different legal branches, pointing those in which it use is more permeable and others where some reticence can be perceived. After that, the paper focuses the analysis in the use of economics in consumer protection branch, to finally use two controversial cases between the Consumers and Users Peruvian Association and two of the more important movie theater chains of the country, in which it is appreciable the lack of use of a law and economics in the motivation of both decisions.